Mitochondrial membrane lipidome defines yeast longevity - Beach, Adam (Impact Journals LLC, 2013)
Our studies revealed that lithocholic acid (LCA), a bile acid, is a potent anti-aging natural compound that in yeast cultured under longevity-extending caloric restriction (CR) conditions acts in synergy with CR to enable a significant further increase in chronological lifespan. Here, we investigate a mechanism underlying this robust longevity-extending effect of LCA under CR. We found that exogenously added LCA enters yeast cells, is sorted to mitochondria, resides mainly in the inner mitochondrial membrane, and also associates with the outer mitochondrial membrane. LCA elicits an age-related remodeling of glycerophospholipid synthesis and movement within both mitochondrial membranes, thereby causing substantial changes in mitochondrial membrane lipidome and triggering major changes in mitochondrial size, number and morphology. In synergy, these changes in the membrane lipidome and morphology of mitochondria alter the age-related chronology of mitochondrial respiration, membrane potential, ATP synthesis and reactive oxygen species homeostasis. The LCA-driven alterations in the age-related dynamics of these vital mitochondrial processes extend yeast longevity. In sum, our findings suggest a mechanism underlying the ability of LCA to delay chronological aging in yeast by accumulating in both mitochondrial membranes and altering their glycerophospholipid compositions. We concluded that mitochondrial membrane lipidome plays an essential role in defining yeast longevity.